Prevalence and risk factors of thrombosis in patients with congenital hyperinsulinism: a retrospective analysis - Albitar, Mohammed Hady; Mariyam, Nida; Alhosainy, Ziad; Alhuthil, Raghad; Nayfeh, Marah; Aldamouni, Maeen; Albitar, Seba; Alsagheir, Afaf (Frontiers in Endocrinology, 2025)
BackgroundCongenital hyperinsulinism (CHI) is a rare but significant cause of persistent neonatal hypoglycemia. While Central Venous Catheters (CVCs) are a known major risk factor for thrombosis in neonates, the evidence linking CHI, catheter use, and thrombotic risk remains limited. This study investigates the prevalence of thrombosis in CHI patients and explores potential contributing factors, such as CVC insertion and infection.MethodsA retrospective cohort study was conducted on 67 patients under 14 years of age who were diagnosed with CHI and treated at King Faisal Specialist Hospital and Research Centre in Riyadh, Saudi Arabia, between 2014 and 2024. Clinical, genetic, and imaging data were analyzed, and associations between thrombosis and risk factors were assessed using univariable analysis.ResultsOf the 67 patients with CHI, 53.7% were female, with a median age at CHI diagnosis of 3 weeks. Genetic analysis revealed ABCC8 mutations as the most frequently identified genetic variant (58.2%). CVCs were used in 61 cases (91.0%), with thrombosis developing in 18.0% of those with CVCs, mostly affecting the vena cava and portal vein. All thrombosis cases were treated with enoxaparin; 63.6% of patients experienced mild, transient complications, including elevated liver enzymes, prolonged partial thromboplastin time (PTT), and thrombocytopenia. A statistically significant association was found between infection and thrombosis (p = 0.001), but no significant correlation was found between specific genetic mutations and thrombosis risk (p > 0.05).ConclusionThese findings underscore the importance of recognizing thrombosis as a potential complication in patients with CHI undergoing CVC placement. Although most cases were successfully managed, early screening and preventive strategies should be considered to minimize thrombotic complications. Future research should focus on optimizing thromboprophylaxis and evaluating additional contributing factors to refine management strategies and improve patient outcomes.